2021
DOI: 10.3390/jmse9080851
|View full text |Cite
|
Sign up to set email alerts
|

Beach Monitoring and Morphological Response in the Presence of Coastal Defense Strategies at Riccione (Italy)

Abstract: The coastal area at Riccione, in the southern Emilia-Romagna littoral region, is exposed to erosive processes, which are expected to be enhanced by climate change. The beach, mostly composed of fine sand, is maintained through various defense strategies, including frequent nourishment interventions for balancing the sediment deficit and other experimental solutions for reducing coastal erosion. Artificial reshaping of the beach and “common practices” in the sediment management redefine the beach morphology and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The data collected in the study area during the one-year experiment suggested that 4D (repeated) surveys are feasible using the employed technologies, since consistent differential bathymetric and reflectivity models of the seafloor were obtained. Morphological changes, not limited to the subaerial beach but extending to the nearshore area, are more significant for evaluating the state and evolution of a coastal area than the shoreline behavior alone, which is very variable and often affected by anthropic bias [38,39]. Comparisons with independent hydrodynamic modeling also suggested an interesting fit between predicted and observed erosional/depositional patterns.…”
Section: Discussionmentioning
confidence: 99%
“…The data collected in the study area during the one-year experiment suggested that 4D (repeated) surveys are feasible using the employed technologies, since consistent differential bathymetric and reflectivity models of the seafloor were obtained. Morphological changes, not limited to the subaerial beach but extending to the nearshore area, are more significant for evaluating the state and evolution of a coastal area than the shoreline behavior alone, which is very variable and often affected by anthropic bias [38,39]. Comparisons with independent hydrodynamic modeling also suggested an interesting fit between predicted and observed erosional/depositional patterns.…”
Section: Discussionmentioning
confidence: 99%
“…In the frame of the STIMARE project (STrategie Innovative, Monitoraggio ed Analisi del Rischio Erosione, www.progettostimare.it, accessed on 12 January 2022) [37], several surveys were performed between 2019 and 2021 to employ and compare different monitoring techniques. One of the goals of the project was to evaluate the morphological response of the studied beach to annual and seasonal wave regimes and to different coastal defense strategies [38].…”
Section: Methodsmentioning
confidence: 99%
“…Surveys were carried out every 6 months on the emerged and submerged beach during the project duration (see [38] for details); the date and techniques of the different surveys are reported in Table 1. In the present work, only data from the emerged and intertidal beaches are shown.…”
Section: Methodsmentioning
confidence: 99%
“…This technique may also be used to forecast how long beach sand will last and how it will respond to storms [8,[12][13][14][15][16]. Measurements of the main sand size characteristics, primarily the median grain size (D 50 ) and the sorting (distribution of sizes around the average, σ), are part of the analysis conducted to investigate coastal processes [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%